Detection and Whole-Genome Characteristics of Bordetella trematum Isolated from Captive Snakes - Magdalena Zając; Inga Bona; Magdalena Skarżyńska; Renata Kwit; Anna Lalak; Ewelina Skrzypiec; Emilia Mikos-Wojewoda; Paulina Pasim; Dominika Wojdat; Weronika Koza; Dariusz Wasyl (Pathogens)
Bordetella trematum is a rare member of the genus Bordetella, primarily associated with human wound infections rather than respiratory diseases. The bacterium has been isolated from various clinical specimens, including ear inflammatory discharge, diabetic ulcers, and chronic wounds. The study aimed to characterize the genomes and antimicrobial resistance (AMR) profiles of B. trematum obtained from the fecal samples of asymptomatic highland eyelash pit vipers (Bothriechis schlegelii). The identification was conducted using MALDI-TOF mass spectrometry and biochemical tests. AMR was assessed using the microbroth dilution method, while whole-genome sequencing was performed on the Illumina NextSeq platform. The isolates displayed characteristic B. trematum biochemical features and demonstrated a resistance to cefotaxime, ciprofloxacin, and trimethoprim, while one also exhibited a resistance to ceftazidime. The whole-genome sequencing and comparison with limited public data revealed a high diversity within B. trematum, reaching >48,000 single nucleotide polymorphisms (SNPs), with 64 SNP differentiating tested snake isolates and thus, being considered epidemiologically unrelated. This is the first report of B. trematum isolated from an animal source in Europe. The findings provide valuable insights into this rare bacterium’s phenotypic and genomic characteristics, addressing an important knowledge gap in its ecology and AMR profile.